Can vaccinia virus be replaced by MVA virus for testing virucidal activity of chemical disinfectants? - Rabenau, Holger F (BioMed Central, 2010)
BACKGROUND: Vaccinia virus strain Lister Elstree (VACV) is a test virus in the DVV/RKI guidelines as representative of the stable enveloped viruses. Since the potential risk of laboratory-acquired infections with VACV persists and since the adverse effects of vaccination with VACV are described, the replacement of VACV by the modified vaccinia Ankara strain (MVA) was studied by testing the activity of different chemical biocides in three German laboratories. METHODS: The inactivating properties of different chemical biocides (peracetic acid, aldehydes and alcohols) were tested in a quantitative suspension test according to the DVV/RKI guideline. All tests were performed with a protein load of 10% fetal calf serum with both viruses in parallel using different concentrations and contact times. Residual virus was determined by endpoint dilution method. RESULTS: The chemical biocides exhibited similar virucidal activity against VACV and MVA. In three cases intra-laboratory differences were determined between VACV and MVA - 40% (v/v) ethanol and 30% (v/v) isopropanol are more active against MVA, whereas MVA seems more stable than VACV when testing with 0.05% glutardialdehyde. Test accuracy across the three participating laboratories was high. Remarkably inter-laboratory differences in the reduction factor were only observed in two cases. CONCLUSIONS: Our data provide valuable information for the replacement of VACV by MVA for testing chemical biocides and disinfectants. Because MVA does not replicate in humans this would eliminate the potential risk of inadvertent inoculation with vaccinia virus and disease in non-vaccinated laboratory workers.